Method development for Cd and Hg determination in biodiesel by electrothermal atomic absorption spectrometry with emulsion sample introduction - Aranda, Pedro Rodolfo (2012)
A novel method for analysis of biodiesel by electrothermal atomic absorption spectrometry is described. This analytical strategy involves sample preparation as emulsions for routine and reliable determination of Cd and Hg. Several experimental conditions were investigated, including emulsion stability and composition, furnace temperature program and matrix modification. Different calibration strategies were also evaluated, being the analyte addition method preferred both for Cd and Hg. The accuracy was verified through comparison with an acid digestion in a microwave closed system. The injection repeatability was evaluated as the average relative standard deviation (R.S.D %) for five successive firings and was better than 4.4% for Cd and 5.4% Hg respectively. The detection limits, evaluated by the 3σ concept of calculation (n=10), were of 10.2 μg kg-1 (0.9 μg L-1) for Hg and 0.3 μg kg-1 (0.04 μg L-1) for Cd. This method was successfully applied to the determination of Cd and Hg in biodiesel samples obtained from local vendors.